Hematological parameters in ewes during lactation in organic farming - Zvonko Antunović; Josip Novoselec; Željka Klir (Poljoprivreda, 2017)
The aim of this investigation is to determine haematological parameters of ewes during lactation in organic farming. Research was carried out with 32 Merinolandschaf ewes in age of 4 years and in third lactation. Sampling of blood from the same ewes was conducted on 20th, 60th and 100th day of lactation. Feeding was based on feed mixture and meadow hay from organic farming. Haematological parameters (number of leukocyte-WBC, erythrocytes-RBC, and platelet-PLT, as well as content of haemoglobin-HGB, haematocrit-HCT, mean corpuscular volume-MCV, the average haemoglobin content in erythrocytes-MCH and mean haemoglobin concentration in erythrocytes-MCHC) in whole blood of ewes and differential blood test (segmented neutrophils-SEG, band cells-NESEG, lymphocytes-LYM, eosinophils- EOS, monocytes-MON and basophils-BAS) were determined. During the lactation significant decrease of RBC (9.36-8.62×1012 L-1), HGB (92.59-86.25 g L-1) and number of BAS (0.41-0.03%) was determined, while MON (0.53-0.06%) decreased until 60th day of lactation. Significant correlations were determined between most of the haematological parameters in blood of ewes in lactation. Significant positive total correlation was determined between RBC and HGB (0.96), very strong correlation between HCT:HGB, RBC:HCT and MON:MCH (0.82, 0.76 and 0.80), as well as strong negative correlation between MCH:MCHC (-0.63). The abovementioned indicated significant interdependence of the most of haematological parameters in ewes during lactation in organic farming.